Staff Assignment Rotation and Project Sustainability in South Sudan - Kanneh , Abraham Ansu; Awolusi, Olawumi Dele (Journal of Education and Vocational Research, 2021)
The primary objective of this study was to determine the existence of a causal relationship between Staff Assignment Rotation vis-à-vis Project Sustainability in South Sudan. The research followed the qualitative methodology predicated on the “philosophical dimensions” of constructivism and interpretivism. The participants for the research consisted of 50 individuals drawn from four population groups: Refugees as the primary beneficiaries, humanitarian workers and project staff. Qualitative data collection was chosen as the research methodology and in-depth interview and focus group discussion as the research techniques in the data collection. Narrative analysis was the method of data analysis. The study revealed that 81 percent of the respondents indicated security as the single most important factor that impacts project sustainability. Staff assignment rotation followed with 16 percent. Data analysis was compartmentalized and looked at the profile of the respondents to see any noticeable variance from the functional perspective. Contextualizing the data helped to balance any perceived unbiased in the responses based on their functional affinity. In addition to Security as the prominent factor that impacts project sustainability, staff rotation, government regulation, and funding could also impact significantly depending on the context. The study recommends a comprehensive review of the current mandatory policy to align the operation management cycle; encompassing the project initiation, planning, implementation, monitoring and closure to the standard assignment length of staff assigned to implement these projects.